Ensuring uniform distribution of heat flow in the process of ultrasonic-convective drying - Jasur E. Safarov; Shaxnoza A. Sultanova; Muhammad R. Najafli; Azamat B. Usenov (PROBLEMS OF ENERGY AND SOURCES SAVING, 2026)
Relevance: optimization of drying processes ensures energy efficiency. Nowadays, this indicator plays a crucial role. This article analyzes the temperature distribution in a drying unit for red beetroot. The analysis was carried out on several varieties of red beetroot. Uniform distribution of the supplied temperature throughout the drying chamber ensures stable process conditions. During the drying process, the initial moisture content of the sample was 86–89%, while the final moisture content reached 15–17%. In these studies, samples with a thickness of 7–8 mm were subjected to ultrasonic treatment at a frequency of 20–30 kHz. Aim: to determine the drying regimes and parameters of red beetroot, as well as to analyze and justify the use of ultrasound during the drying process. Methods: comparative analysis methods of international practices were applied. Results: it was found that at a chamber temperature of 55 °C, the optimal drying regime was achieved. In addition, our study analyzed the effect of ultrasound, which was found to have a positive impact on accelerating diffusion and improving the distribution of heat during the drying process.